Antifungal treatment in haematological and oncological patients: Need for quality assessment in routine care. Issue 7 (26th April 2018) - Lachenmayr, Sarah J.; Berking, Sophie; Horns, Heidi; Strobach, Dorothea; Ostermann, Helmut; Berger, Karin
Summary: Invasive fungal infections in haematological and oncological patients have a major impact on morbidity, mortality and treatment costs. Therefore, rational use of antifungal agents is important for optimal patient care and resource use. The study's objective was to analyse antifungal usage in a German tertiary teaching hospital, department of haematology and oncology, to evaluate quality of antifungal treatment and to assess the need for an antifungal stewardship programme. This retrospective observational study included patients ≥18 years receiving systemic antifungals for prophylaxis or therapy of invasive fungal infection between January and June 2016. Appropriateness of antifungal prescriptions was evaluated in accordance with guidelines of the German Society of Haematology and Oncology (DGHO) and drug labelling. In total, 104/1278 (8.1%) patients received antifungals. One hundred seventy‐one antifungals were prescribed: 48 for prophylaxis, 104 for empirical and 19 for targeted therapy. In 127 (74.3%) prescriptions, indication was appropriate, and in 132 (77.2%), choice of drug. Antifungals were correctly dosed in 131 prescriptions (76.6%). Thirty‐four antifungals (20.0%) were co‐administrated with interacting drugs (5 mild to moderate, 29 severe interactions). Results of this analysis demonstrate that use of systemic antifungals in routine care differs in a substantial number of patients from guideline and labelling recommendations. To optimise antifungal use, the implementation of antifungal stewardship programmes seems to be justified.